Methodische Untersuchungen zur numerischen Simulation der Kabinenakustikmit FEM - Yi Qiao (2013)
It is very important to predict the acoustic behavior of the fuselage cabin for the noise control. Such coupled fluid-structure interaction problems can be solved by numerical simulation using finite element method. Following the reciprocity principle is introduced and tested on a simple model to verify the accuracy. Then a practical model of a fuselage cabin a is studied. On the basis of the sound pressure level results from each ear position of passengers, reciprocity principle and also other methods are employed for the peak frequencies to evaluate the structure parts that have most influence on the acoustic response. After that, the structure is improved base on the analysis results.